Two different species of murein transglycosylase in Escherichia coli. - Mett, H (1980)
We demonstrated that Escherichia coli murein transglycosylase exists in two forms. After mechanical disruption of the cells, one form was found in the soluble fraction and the other, in the cell envelope. The two enzymes differed with respect to molecular weight, isoelectric point, solubility in aqueous buffers, and to some extent in their requirements for maximal catalytic activity. The molecular weight of the membrane-bound transglycosylase (35,000) was half that of the soluble enzyme. Whether the high-molecular-weight soluble protein is a precursor of the membrane-bound enzyme species remains to be elucidated.